Proceedings of the Seventh International Conference on Educational Data Mining (EDM) (7th, London, United Kingdom, July 4-7, 2014) - Stamper, John, Ed; Pardos, Zachary, Ed; Mavrikis, Manolis, Ed; McLaren, Bruce M., Ed (International Educational Data Mining Society, 2014)
The 7th International Conference on Education Data Mining held on July 4th-7th, 2014, at the Institute of Education, London, UK is the leading international forum for high-quality research that mines large data sets in order to answer educational research questions that shed light on the learning process. These data sets may come from the traces that students leave when they interact, either individually or collaboratively, with learning management systems, interactive learning environments, intelligent tutoring systems, educational games or when they participate in a data-rich learning context. The types of data therefore range from raw log files to eyetracking devices and other sensor data. Being hosted in London, UK the theme of the conference is "Big Data--Big Ben--Education Data Mining for Big Impact in Teaching and Learning". In this seventh year of EDM conferences, it is clear that the field is continuing to grow at a rapid pace. With renewed focus on education driven by big data learning analytics has put the EDM field in the center of growing interest. Traditional educational technologies, intelligent tutoring systems, educational games, and learning management systems all continue to generate growing amounts of data that are becoming available for analysis. The new interest in MOOCs and their promise to reach thousands or even hundreds of thousands of students per class requires techniques for feedback and grading that are being researched in the EDM domain. The conference submissions this year also continue to grow. A tremendous amount of work has gone into bringing this conference together, and the following are presented: (1) The Field of EDM: Where We Came from and Where We're Going (Joseph Beck); (2) Generative Adaptivity for Optimization of the Learning Ecosystem (Zoran Popovic; (3) 150K+ Online Students at a Time: How to Understand What's Happening in Online 4 Learning (Daniel Russell); (4) Adaptive Practice of Facts in Domains with Varied Prior Knowledge (Jan Papoušek, Radek Pelánek and Vít Stanislav); (5) Alternating Recursive Method for Q-Matrix Learning (Yuan Sun, Shiwei Ye, Shunya Inoue and Yi Sun); (6) Application of Time Decay Functions and the Elo System in Student Modeling (Radek Pelánek); (7) Causal Discovery with Models: Behavior, Affect, and Learning in Cognitive Tutor Algebra (Stephen Fancsali); (8) Choice-Based Assessment: Can Choices Made in Digital Games Predict 6th-Grade Students' Math Test Scores? (Min Chi, Daniel Schwartz, Kristen Pilner Blair and Doris B. Chin); (9) Comparing Expert and Metric-Based Assessments of Association Rule Interestingness (Diego Luna Bazaldua, Ryan Baker and Maria Ofelia San Pedro); (10) Different Parameters - Same Prediction: An Analysis of Learning Curves (Tanja Käser, Kenneth Koedinger and Markus Gross); (11) Discovering Gender-Specific Knowledge from Finnish Basic Education Using PISA Scale Indices (Mirka Saarela and Tommi Kärkkäinen); (12) EduRank: A Collaborative Filtering Approach to Personalization in E-Learning (Avi Segal, Ziv Katzir, Kobi Gal, Guy Shani and Bracha Shapira); (13) Exploring Differences in Problem Solving with Data-Driven Approach Maps (Michael Eagle and Tiffany Barnes); (14) General Features in Knowledge Tracing: Applications to Model Multiple Subskills, Temporal Item Response Theory, and Expert Knowledge (José González-Brenes, Yun Huang and Peter Brusilovsky); (15) Generating Hints for Programming Problems Using Intermediate Output ( Barry Peddycord III, Andrew Hicks and Tiffany Barnes); (16) Integrating Latent-Factor and Knowledge-Tracing Models to Predict Individual Differences in Learning (Mohammad Khajah, Rowan Wing, Robert Lindsey and Michael Mozer); (17) Interpreting Model Discovery and Testing Generalization to a New Dataset (Ran Liu, Elizabeth A. McLaughlin and Kenneth R. Koedinger); (18) Learning Individual Behavior in an Educational Game: A Data-Driven Approach (Seong Jae Lee, Yun-En Liu and Zoran Popovic); (19) Predicting Learning and Affect from Multimodal Data Streams in Task-Oriented Tutorial Dialogue (Joseph Grafsgaard, Joseph Wiggins, Kristy Elizabeth Boyer, Eric Wiebe and James Lester); (20) Sentiment Analysis in MOOC Discussion Forums: What does It Tell Us? (Miaomiao Wen, Diyi Yang and Carolyn Rose); (21) The Effect of Mutual Gaze Perception on Students' Verbal Coordination (Bertrand Schneider and Roy Pea); (22) The Opportunities and Limitations of Scaling Up Sensor-Free Affect Detection (Michael Wixon, Ivon Arroyo, Kasia Muldner, Winslow Burleson, Cecil Lozano and Beverly Woolf); (23) The Problem Solving Genome: Analyzing Sequential Patterns of Student Work with Parameterized Exercises (Julio Guerra, Shaghayegh Sahebi, Peter Brusilovsky and Yu-Ru Lin); (24) Trading Off Scientific Knowledge and User Learning with Multi-Armed Bandits (Yun-En Liu, Travis Mandel, Emma Brunskill and Zoran Popovic); (25) Vertical and Stationary Scales for Progress Maps (Russell Almond, Ilya Goldin, Yuhua Guo and Nan Wang); (26) Visualization and Confirmatory Clustering of Sequence Data from a Simulation- Based Assessment Task (Yoav Bergner, Zhan Shu and Alina von Davier); (27) Who's in Control?: Categorizing Nuanced Patterns of Behaviors within a Game- Based Intelligent Tutoring System (Erica Snow, Laura Allen, Devin Russell and Danielle McNamara); (28) Acquisition of Triples of Knowledge from Lecture Notes: A Natural Language Processing Approach (Thushari Atapattu, Katrina Falkner and Nickolas Falkner); (29) Towards Assessing Students' Prior Knowledge from Tutorial Dialogues (Dan Stefanescu, Vasile Rus and Art Graesser); (30) Assigning Educational Videos at Appropriate Locations in Textbooks (Marios Kokkodis, Anitha Kannan and Krishnaram Kenthapadi) (31) Better Data Beats Big Data (Michael Yudelson, Stephen Fancsali, Steven Ritter, Susan Berman, Tristan Nixon and Ambarish Joshi); (32) Building a Student At-Risk Model: An End-to-End Perspective (Lalitha Agnihotri and Alexander Ott); (33) Can Engagement be Compared? Measuring Academic Engagement for Comparison (Ling Tan, Xiaoxun Sun and Siek Toon Khoo); (34) Comparison of Algorithms for Automatically Building Example-Tracing Tutor Models (Rohit Kumar, Matthew Roy, Bruce Roberts and John Makhoul); (35) Computer-Based Adaptive Speed Tests (Daniel Bengs and Ulf Brefeld); (36) Discovering Students' Complex Problem Solving Strategies in Educational Assessment (Krisztina Tóth, Heiko Rölke, Samuel Greiff and Sascha Wüstenberg); (37) Discovering Theoretically Grounded Predictors of Shallow vs. Deep-Level Learning (Carol Forsyth, Arthur Graesser, Philip I. Pavlik Jr., Keith Millis and Borhan Samei); (38) Domain Independent Assessment of Dialogic Properties of Classroom Discourse (Borhan Samei, Andrew Olney, Sean Kelly, Martin Nystrand, Sidney D'Mello, Nathan Blanchard, Xiaoyi Sun, Marci Glaus and Art Graesser); (39) Empirically Valid Rules for Ill-Defined Domains (Collin Lynch and Kevin Ashley); (40) Entropy: A Stealth Measure of Agency in Learning Environments (Erica Snow, Matthew Jacovina, Laura Allen, Jianmin Dai and Danielle McNamara); (41) Error Analysis as a Validation of Learning Progressions (Brent Morgan, William Baggett and Vasile Rus); (42) Exploration of Student's Use of Rule Application References in a Propositional Logic Tutor (Michael Eagle, Vinaya Polamreddi, Behrooz Mostafavi and Tiffany Barnes); (43) Exploring Real-Time Student Models Based on Natural-Language Tutoring Sessions (Benjamin Nye, Mustafa Hajeer, Carolyn Forsyth, Borhan Samei, Xiangen Hu and Keith Millis); (44) Forum Thread Recommendation for Massive Open Online Courses (Diyi Yang, Mario Piergallini, Iris Howley and Carolyn Rose); (45) Investigating Automated Student Modeling in a Java MOOC (Michael Yudelson, Roya Hosseini, Arto Vihavainen and Peter Brusilovsky); (46) Mining Gap-Fill Questions from Tutorial Dialogues (Nobal B. Niraula, Vasile Rus, Dan Stefanescu and Arthur C. Graesser); (47) Online Optimization of Teaching Sequences with Multi-Armed Bandits (Benjamin Clement, Pierre-Yves Oudeyer, Didier Roy and Manuel Lopes); (48) Predicting MOOC Performance with Week 1 Behavior (Suhang Jiang, Adrienne Williams, Katerina Schenke, Mark Warschauer and Diane O'Dowd); (49) Predicting STEM and Non-STEM College Major Enrollment from Middle School Interaction with Mathematics Educational Software (Maria Ofelia San Pedro, Jaclyn Ocumpaugh, Ryan Baker and Neil Heffernan); (50) Quantized Matrix Completion for Personalized Learning (Andrew Lan, Christoph Studer and Richard Baraniuk); (51) Reengineering the Feature Distillation Process: A Case Study in Detection of Gaming the System (Luc Paquette, Adriana de Carvahlo, Ryan Baker and Jaclyn Ocumpaugh); (52) SKETCHMINER: Mining Learner-Generated Science Drawings with Topological Abstraction (Andy Smith, Eric N. Wiebe, Bradford W. Mott and James C. Lester); (53) Teachers and Students Learn Cyber Security: Comparing Software Quality, Security (Shlomi Boutnaru and Arnon Hershkovitz); (54) Testing the Multimedia Principle in the Real World: A Comparison of Video vs. Text Feedback in Authentic Middle School Math Assignments (Korinn Ostrow and Neil Heffernan); (55) The Importance of Grammar and Mechanics in Writing Assessment and Instruction: Evidence from Data Mining (Scott Crossley, Kris Kyle, Laura Allen and Danielle McNamara); (56) The Long and Winding Road: Investigating the Differential Writing Patterns of High and Low Skilled Writers (Laura Allen, Erica Snow and Danielle McNamara); (57) The Refinement of a Q-Matrix: Assessing Methods to Validate Tasks to Skills Mapping (Michel Desmarais, Behzad Beheshti and Peng Xu); (58) Tracing Knowledge and Engagement in Parallel in an Intelligent Tutoring System (Sarah Schultz and Ivon Arroyo); (59) Tracking Choices: Computational Analysis of Learning Trajectories (Erica Snow, Laura Allen, G.Tanner Jackson and Danielle McNamara); (60) Unraveling Students' Interaction Around a Tangible Interface Using Gesture Recognition (Bertrand Sc